MISSION-DRIVEN HRM IN NON-PROFIT ORGANISATION: A SYSTEMATIC REVIEW OF PLANNING PRACTICES AND CHALLENGES - Benny Nur Miftahul Ulum; Tika Widiastuti; Ari Prasetyo; Arva Athallah Susanto (Airlangga International Journal of Islamic Economics and Finance, 2026)
This study examines human resource (HR) planning in non-profit organisations, focusing on mission-driven approaches to address the sector’s unique challenges. Non-profits often operate under budget constraints, face high turnover, and depend heavily on volunteer labour, necessitating HR strategies that move beyond conventional models. Using a Systematic Literature Review (SLR), we analysed 47 peer-reviewed studies published between 2014 and 2024, identified through the Scopus database. A PRISMA-based screening process guided the selection, ensuring transparency and replicability. The synthesis of the literature reveals five key themes: (1) integration of Corporate Social Responsibility (CSR) into HRM, (2) the role of social economy and innovation in public services, (3) welfare-focused leadership, (4) ethical engagement to foster commitment, and (5) volunteer performance management. Quantitative mapping also shows diverse geographic distributions and methodological approaches across the studies. The findings highlight the importance of aligning HRM strategies with organisational values to sustain workforce motivation and maximise social impact. The study contributes by offering a holistic HR planning framework tailored to non-profits, providing both theoretical insights and practical guidance for enhancing sustainability and advancing the sector’s mission.